Anemia on Admission Is an Independent Predictor of Long-Term Mortality in Hip Fracture Population: A Prospective Study With 2-Year Follow-Up. Issue 5 (February 2016) - Zhang, Licheng; Yin, Pengbin; Lv, Houchen; Long, Anhua; Gao, Yuan; Zhang, Lihai; Tang, Peifu
Abstract : Abstract: Anemia is a disputable factor for long-term mortality in hip fracture population in previous studies. Previous studies indicated that the level of hemoglobin (Hb) might fluctuate due to various factors, such as comorbidities and in-hospital interventions, and the changing level of Hb, may lead to discordance diagnosis of anemia and thus to the conflicting conclusions on prognostic value of anemia. So in this study, we aim to compare factors affecting the diagnosis of anemia at different time-points, admission, postoperation, and discharge, and to determine which the time point is most suitable for mortality prediction. This prospective cohort study included 1330 hip fracture patients from 1 January 2000 to 18 November 2012. Hb levels at 3 different time points, such as admission, postoperation, and discharge, were collected and used to stratify the cohort into anemia and nonanemia groups. Candidate factors including commodities, perioperative factors, blood transfusion, and other in-hospital interventions were collected before discharge. Logistic regression analyses were performed to detect risk factors for anemia for the 3 time points separately. Kaplan–Meier and multivariate Cox regression analyses were used to evaluate the association between anemia and 2-year mortality. Factors affecting the diagnosis of anemia were different for the 3 time points. Age, female sex, American Society of Anesthesiologists score (ASA), and intertrochanteric fracture were associated with admission anemia, while surgical procedure, surgical duration, blood transfusion, blood loss during the operation, and drainage volume were major risk factors for postoperation anemia. Cox proportional-hazards regression analysis suggested that the risk of all-cause mortality was higher in the anemia group on admission (1.680, 95%CI: 1.201–2.350, P < 0.01), but not postoperation or on discharge, after adjustment for confounding factors. Our study showed that risk factors for anemia varied at different time points, and therapy interventions would greatly affect the status of postoperation and discharge anemia in hip fracture patients. The take-home message is when anemia is used for mortality prediction in these patients, a specific time point should be chosen. We suggest that only admission anemia should be used for mortality prediction, but not postoperation nor discharge anemia.